DIFFERENCES IN QUALITY OF LIFE: LONGITUDINAL STUDY WITH CANCER PATIENTS RECEIVING CHEMOTHERAPY TREATMENT - Terol, M.Carmen; López- Roig, Sofía; Rodríguez-Marín, Jesús; Pastor, M.Angeles; Mora, María; Martín-Aragón, Maite; Leyda-Menéndez, José Ignacio; Neipp, M.Carmen; Lizón, José (Anales de Psicología / Annals of Psychology, 2000)
The diagnosis and treatment of cancer causes several psychological and social responses which affect patient’s quality of life. Quality of life is a multidimensional construct including functional ability, symptoms from disease and treatment, social and psychological dimensions. In this study we assess the quality of life and anxiety and depression of cancer patients group receiving chemotherapy. 21 patients were interviewed twice. We collected information when they started the treatment and when they were finished it. The Physical condition was associated with the Global Quality of Life, and both with depression. Significant differences appeared in Physical Condition between phase 1 and 2 in this study. Symptoms of Disease and Economical Impact were associated with anxiety or with depression in both phases of this study. Social Impact correlated to depression and anxiety in phase 1, and Functional Disability with global Quality of Life in phase 2.